Al-/Ga-Doped ZnO Window Layers for Highly Efficient Cu2ZnSn(S,Se)(4) Thin Film Solar Cells - Seo, Se Won; Seo, Jung Woo; Kim, Donghwan; Cheon, Ki-Beom; Lee, Doh-Kwon; Kim, Jin Young (AMER SCIENTIFIC PUBLISHERS, 2018)
The successful use of Al-/Ga-doped ZnO (AGZO) thin films as a transparent conducting oxide (TCO) layer of a Cu2ZnSn(S,Se)(4) (CZTSSe) thin film solar cell is demonstrated. The AGZO thin films were prepared by radio frequency (RF) sputtering. The structural, crystallographic, electrical, and optical properties of the AGZO thin films were systematically investigated. The photovoltaic properties of CZTSSe thin film solar cells incorporating the AGZO-based TCO layer were also reported. It has been found that the RF power and substrate temperature of the AGZO thin film are important factors determining the electrical, optical, and structural properties. The optimization process involving the RF power and the substrate temperature leads to good electrical and optical transmittance of the AGZO thin films. Finally, the CZTSSe solar cell with the AGZO TCO layer demonstrated a high conversion efficiency of 9.68%, which is higher than that of the conventional AZO counterpart by 12%.
Keywords: ELECTRODEPOSITION; TEMPERATURE; FABRICATION; DEPOSITION; DIODES; OXYGEN; GAAS; AZO; GZO